1994
DOI: 10.1080/00050069408257328
|View full text |Cite
|
Sign up to set email alerts
|

The skills-based model of counselling training: A review of the evidence

Abstract: hile skills-based approaches to basic counselling training dominate the field, they have been criticised W on four counts: (a) lack of evidence as to effectiveness in improving interview performance, (b) lack of evidence of skills retention and transfer, (c) failure to take into account trainees' individual differences in counselling aptitude, and (d) failure to take into account trainees' underlying cognitive structures and processes. A review of the literature suggests that the first two criticisms can be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Some approaches, termed skills-training models, break up complex clinical skills into their simpler constituent elements, which are then taught to trainees in a step-wise manner through demonstration, observation, role play, and feedback techniques. Skills-based models are best known in the counselling domain, where they have been proven to enhance trainee skills in communication and counselling (Baker & Daniels, 1989;McLennan, 1994). The OBAS shares with such models the preference to analyse complex behaviours into more specific objectives, and in their stepwise approach to skills training.…”
Section: The Obas and Skills-training Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some approaches, termed skills-training models, break up complex clinical skills into their simpler constituent elements, which are then taught to trainees in a step-wise manner through demonstration, observation, role play, and feedback techniques. Skills-based models are best known in the counselling domain, where they have been proven to enhance trainee skills in communication and counselling (Baker & Daniels, 1989;McLennan, 1994). The OBAS shares with such models the preference to analyse complex behaviours into more specific objectives, and in their stepwise approach to skills training.…”
Section: The Obas and Skills-training Modelsmentioning
confidence: 99%
“…The emphasis on clinical supervision in the international literature is not reflected in the local context, and an extensive review yielded no more than a limited number of references (e.g., Clark, 1990;Cross, 1983;Hewson, 1992;McLennan, 1994;Penney, 1985;Pitty, 1994). This is not a gratifying result, especially when viewed alongside other professional developments in the country.…”
mentioning
confidence: 99%
“…The research conducted so far has focused on evaluating the educational benefits of communication skills training (cf., Baker and Daniels 1989;Baker et al 1990;McLennan 1994) and the impact of discrete counselor behaviors on specific counseling processes (cf., Hill 2001). This research has been primarily of an analogue nature and has not linked delivery of particular counseling skills to validated measures of client improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Yet though reasonable, research has not yet established the therapeutic benefits of basic attending and listening skills in the context of very short-term counseling. While it is has been demonstrated that basic attending and listening skills can be acquired and even retained by counseling students (e.g., Baker and Daniels 1989;McLennan 1994), little research has attempted to link delivery of these specific skills to validated outcomes with actual clients (e.g., Roffers et al 1988). In fact, nearly all of the studies attesting to the value of very brief therapy (1-3 sessions) are based on solution-focused therapy or some derivative thereof (cf., Bloom 2001;Miller 2008;Perkins and Scarlett 2008;Talmon 1990); models in which problem exploration is explicitly eschewed in favor of quickly working toward solutions to clients' most pressing problems.…”
Section: Termination Stagementioning
confidence: 98%
“…Even when specific counseling sessions are the focus of analysis and when experts judge counselor behavior, few valid and reliable measures of actual counseling skills exist. Virtually none of the measures that were analyzed in literature reviews and meta-analyses by Alberts and Edelstein (1990), McLennan (1994), Ponterotto and Furlong (1985), and Shaw and Dobson (1988) had been adequately tested for construct validity. A full 88% of the rating scales reviewed by Ponterotto and Furlong relied only on face validity.…”
Section: Absence Of Validity Checksmentioning
confidence: 99%